Natural Resources – Food Nexus: Food-Related Environmental Footprints in the Mediterranean Countries - Lacirignola, Cosimo; Capone, Roberto; Debs, Philipp; El Bilali, Hamid; Bottalico, Francesco (Frontiers in Nutrition, 2014)
Immediate action is required in the Mediterranean to address environmental degradation that is mainly driven by consumption patterns. Increasing stress on biological and social systems is put by unsustainable consumption patterns. Food consumption patterns are important drivers of environment degradation. The objective of this review paper is to explore natural resources-food nexus in the Mediterranean region by highlighting the environmental footprints of the current consumption and production patterns. Secondary data from different sources such as FAOSTAT, the World Bank, Water Footprint Network (WFN) and Global Footprint Network were used to analyse the situation in 21 Mediterranean countries. The region faces many environmental challenges e.g. land degradation, water scarcity, environment pollution, biodiversity loss and climate change. The current consumption patterns imply high ecological, carbon and water footprints of consumption and unfavourable national virtual water balances. Food Balance Sheets data show that the contribution of vegetal and animal-based food product groups to food supply is variable among the Mediterranean countries. This has implications also in terms of the WF of food supply, which was calculated for Bosnia, Egypt, Italy, Morocco and Turkey. The WF of the current diet resulted lower than that of the proposed Mediterranean one in the case of Italy. There is a strong scientific evidence supporting assumption that it is so also for other Mediterranean countries. The Mediterranean is characterised by a high resource use intensity that is further exacerbated by food losses and waste (FLW). In fact, FLW implies the loss of precious resources (water, land, energy) and inputs (fertilisers). Therefore, it is crucial to increase adherence to the traditional Mediterranean diet and to reduce FLW in order to foster transition to more sustainable food consumption patterns thus reducing pressure on the scarce resources of the Mediterranean region.